Asian Youth Cultural Expression, Creativity, and Innovation on YouTube - Hidayat, Zinggara (FISIP Universitas Atma Jaya Yogyakarta, 2017)
Groups and intercommunity interactions form global society. This study aims to describe the global aspect in the local cultural expression or vice-versa on YouTube videos. The cultural expressions include language, dress, cuisine, festivals and leisure creativities, social customs and lifestyle. Qualitative descriptive approach is used to analyze ten videos made by Southeast Asian young people. This research found that the locality expression goes global. Cultural expressions communicate the cross-cultural understanding especially in mainland, peninsula, and islands. This youth creativity describes the â€œglocalityâ€ of Indian, Arabic, Chinese, Malay, Java, and the West cultures.